The Effect Of Confidence Level On Problem-Solving Ability On The Topic Of Comparative Trigonometry: A Study On High School Students - Destri Handayani; Kusnandi Kusnandi (Eduvest - Journal of Universal Studies, 2025)
This research addresses the challenges students face in understanding the concept of trigonometric comparison. This problem is often considered as one of the weak areas in mathematics learning. The purpose of this research is to identify the influence of students' confidence level can affect problem solving ability related to trigonometry material for a research study on high school students. The research used descriptive qualitative method through in-depth interviews to analyze the exam results with the students who became the research subjects and observed the students as they solved trigonometry problems. This study concluded that: 1) students who have high self-confidence can fulfill the criteria according to the indicators of problem solving ability according to Polya's indicators, namely being able to understand the problem, being able to make a plan, completing the plan and being able to look at the answer again. 2) students who have moderate self-confidence can meet the criteria according to Polya's problem solving ability indicators, namely being able to understand the problem, can make a plan, complete the plan, but have not been able to see all the answers, and 3) students who have low self-confidence have difficulty understanding, unable to plan, and complete the solution plan and cannot see all the answers.